2005
DOI: 10.1021/la046842j
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies of the Intermolecular Interactions of Congo Red and Tinopal CBS with Modified Cellulose Fibers

Abstract: The adsorption of Congo red and tinopal CBS dyes on cellulose fibers was investigated using electronic absorption and fluorescence spectroscopies. Hydrogen bonds appear to be relevant for the dye-fiber interactions as indicated by the solvatochromism of Congo red in water, methanol, and dimethyl sulfoxide solutions, and when adsorbed on cellulose fibers. We also demonstrate that electrostatic interactions play an important role in the dye-medium interaction, through the analysis of absorption spectra of Congo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 39 publications
6
34
0
Order By: Relevance
“…The red-shift of λ max due to the CR aggregation has also been widely reported [42][43][44]. For example, Yamaki et al [45] have reported the λ max of the CR red-shift to 504 nm upon forming aggregates in a layer-by-layer nanostructured film under a given condition.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 66%
“…The red-shift of λ max due to the CR aggregation has also been widely reported [42][43][44]. For example, Yamaki et al [45] have reported the λ max of the CR red-shift to 504 nm upon forming aggregates in a layer-by-layer nanostructured film under a given condition.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 66%
“…Spectrum of AG25 absorbed on CAES is very different: the band is largely broadened toward the short wavelength and no obvious peak position can be seen. For the pH and ion strength are insensitive to the max of dyes, this shift indicates strong hydrogen bonding between dyes and adsorbent [41]. The trend is also apparent for AR18 ( max = 517 nm in DMSO, max = 508 nm in methanol, max = 506 nm in water and a broad band for the AR18 adsorbed onto CAES), implied strong hydrogen bonding between AR18 and CAES.…”
Section: Hydrogen Bonding and Steric Hindrancementioning
confidence: 83%
“…In order to address such question, the present paper describes an attempt to model the adsorption of the direct Congo red (CR) dye on model cellulose crystals. Even if the staining of cellulose with CR is not used industrially for toxicological and colour stability reasons, its adsorption on cellulose and other polysaccharides, which is used for analytical purpose, is well documented (Wood 1980(Wood , 1982Yamaki et al 2005). In a molecular mechanics modelling study, Woodcock et al (1995), have investigated the docking of CR molecules on the hydrophilic faces of crystalline cellulose.…”
Section: Introductionmentioning
confidence: 99%